Pembelajaran Sejarah Melalui Nilai-Nilai Kesenian Degung di Kelas X IPS 1 MA Negeri 2 Ciamis Tahun Ajaran 2022-2023 - Pupu Maspuroh; Sri Pajriah; Aan Suryana (Universitas Galuh, 2023)
History learning materials are generally based on textbooks and use very little developer material. This is the background of this research regarding the use of material for developing Degung artistic values in learning history. To find out what are the values of Degung art and how to use Degung artistic values in learning history in class X IPS 1 MA Negeri 2 Ciamis. Qualitative research methods with literature and field studies include observation, interviews and documentation. Data analysis used is data reduction, data presentation and verification. The results of the research show that the values contained in Degung art are religious values, historical values, social values, ethical values, creative values and aesthetic values. The use of material for developing Degung artistic values in history lessons must be in accordance with the learning objectives adapted to the teacher's teaching style. After designing the RPP and adding material to the power point slides the use of developer material has been realized and it is very possible to use developer material. Obstacles such as readjustment of learning outcomes, the use of developer material is a new thing, time constraints and student responses which later as teacher educators try to deal with these obstacles so that the results are that the teacher is greatly helped by the presence of developer material and students are enthusiastic about learning.